Urban Flood Risk, Interventions, and The Role Of City Planning - Whittingham, Neil (International Journal of Built Environment and Scientific Research, 2017)
This paper is a reflection upon the issue of urban flooding, attempts to adapt to it and strategic risk reduction measures of those with responsibility for planning at the level of the city region. Following the introduction, flooding hazards are considered within the context of global environmental processes and rapid urbanisation, and the paper has a discussion of both theoretical and policy perspectives to urban flood risk and vulnerability. Consideration is then given to a broad range of potential interventions that could be available to stakeholders, before, during or after a flooding event, whether the measure would be undertaken by a government, member(s) of the community or the private sector. Finally, in the context of international policy guidance, consideration is given to the role that city planners could make in addressing the risk of flooding emergencies through more strategic, medium and long-term approaches. The paper concludes that collaborative forms of governance with the full engagement of the community are essential for disaster risk resilience